High harmonic generation in monolayer MoS2 controlled by resonant and near-resonant pulses on ultrashort time scales - Pavel Peterka; Artur O. Slobodeniuk; Tomáš Novotný; Pawan Suthar; Miroslav Bartoš; František Trojánek; Petr Malý; Martin Kozák (APL Photonics, 2023)
We report on experimental investigation of nonperturbative high harmonic generation (HHG) in monolayer MoS2 in the ultraviolet spectral region driven by mid-infrared light. We study how the HHG is influenced by pre-excitation of the monolayer using resonant and near-resonant pulses in a pump–probe-like scheme. The resonant light creates high density exciton population. Due to ultrafast dephasing caused by electron–electron scattering, the HHG is suppressed in the presence of pre-excited carriers. In the case of near-resonant excitation with photon energy below the exciton transition, the dynamics of the observed suppression of the HHG yield contains a fast component, which is a consequence of momentum scattering at carriers, which are excited by two-photon transition when the two pulses temporally overlap in the sample. This interpretation is supported by comparing the experimental data with theoretical calculations of the two-photon absorption spectrum of the MoS2 monolayer. This work demonstrates a possibility to control HHG in low-dimensional materials on ultrashort timescales by combining the driving strong-field pulse with a weak near-resonant light.